Effects of corn gluten feed and dried distillers grain on goat growth and performance - Siburt, Taylor K.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
This study was aimed to provide information about inclusion of specific diet ingredients for Boer type meat goats. Due to the lack of published data producers are limited the information to make economic decisions when determining what type of feed to use. We evaluated the ability for corn gluten feed (CGF) and Dried Distillers Grains with Soluble (DDGS) to replace soybean meal (SBM) on a feed cost efficiency basis. Seventy-five Boer-type goats were fed one of five dietary treatments for a 35-day period. The goats had an average starting weight at 26.9 kg (±0.2 kg) and approximately 70 days of age. Three goats were randomly allocated to treatment pens with five pens per treatment in a completely randomized design. The CGF was substituted for SBM in five isocaloric and isonitrogenous treatments: 1) soybean meal; 2) 100% DDGS/0% CGF; 3) 66% DDGS/33% CGF; 4) 33% DDGS/66% CGF; 5) 0% DDGS/100% CGF. Goat weights and feed disappearance was recorded weekly. Cost was calculated to find the most cost-efficient feeding option. The cheapest option to get one kilogram of gain was 100% DDGS at $1.64/kg. The prices of the other feed mixtures included $1.72/kg (SBM), $1.73/kg (33% CGF), and $1.75/kg (66% CGF). The more costly option to get one kilogram of gain was 100% CGF at $1.89/kg. Corn gluten feed did not affect the final day body weight (P>0.05) nor did it affect average daily gain (ADG). The ADG for each treatment included 0.152 kg (SBM), 0.146 kg (100% DDGS), 0.128 kg (33% CGF), 0.132 kg (66% CGF), and 0.126 kg (100% CGF). In summary, CGF and DDGS can be used as an economic replacement in Boer-type goat diets.
Keywords: Spring 2019